X-bar parameter triggering: approach to enhance syntax proficiency - Saeipoor, Neda; Mustapha, Ghazali (IDOSI Publications, 2011)
This study investigates the effectiveness of presenting syntax parameters in the order of availability based on the X-bar tree hierarchy. It was supposed that presenting and emphasizing the parameters in the order that they emerge in the X-bar tree and “triggering” the X-bar parameters may enhance syntax proficiency. The study was conducted through an English language course attended by 30 participants chosen based on their homogeneous grammar proficiency. The rules were presented to the participants’ directly through examples and grammar exercises and indirectly through class activities. Inferential statistic procedures were used to compare the means of the results for the tests conducted during the course based on the equivalent time series. A significant difference was found in the means and accordingly it was concluded that triggering the X-bar parameters may be used as an effective way to enhance the grammar proficiency in adult second language speakers.